2019
DOI: 10.1093/ndt/gfz242
|View full text |Cite
|
Sign up to set email alerts
|

The urinary proteomics classifier chronic kidney disease 273 predicts cardiovascular outcome in patients with chronic kidney disease

Abstract: Background The urinary proteomic classifier chronic kidney disease 273 (CKD273) is predictive for the development and progression of chronic kidney disease (CKD) and/or albuminuria in type 2 diabetes. This study evaluates its role in the prediction of cardiovascular (CV) events in patients with CKD Stages G1–G5. Methods We applied the CKD273 classifier in a cohort of 451 patients with CKD Stages G1–G5 followed prospectively f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…Peptide biomarkers can also provide insight into CKD diagnosis and progression. In a recent study, 273 specific urinary peptides (CKD273 classifier) were identified as reliable predictors of CKD progression [26] and cardiovascular events in CKD [27]. In this study, we hypothesized that if some proteins showed significant quantitative changes in patient serum and correlated with well-established markers, then they would be potential biomarkers for CKD diagnosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Peptide biomarkers can also provide insight into CKD diagnosis and progression. In a recent study, 273 specific urinary peptides (CKD273 classifier) were identified as reliable predictors of CKD progression [26] and cardiovascular events in CKD [27]. In this study, we hypothesized that if some proteins showed significant quantitative changes in patient serum and correlated with well-established markers, then they would be potential biomarkers for CKD diagnosis.…”
Section: Discussionmentioning
confidence: 97%
“…Our target proteomics results are compared with previously reported data from studies of different renal pathologies in Table 3. AAT, which is supposed to have anti-inflammatory properties, belongs to the group of serine proteinases [27]. Exogenous AAT inhibited apoptosis and inflammation in renal reperfusion [28] and reduced the urine kidney injury molecule-1 (KIM-1) concentration [30].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study could be indirectly confirmed with previous studies because some fetuin-A peptides are also included in the peptide-based classifier CKD273 [ 31 ]. This classifier was validated in several studies for the early diagnosis and prediction of CKD progression [ 32 , 33 ] as well as prediction of the cardiovascular outcome in diabetes patients [ 34 ]. In general, these studies showed that using a large number of clinical and proteomics data available at the Human Urinary Proteome Database can be very useful for the evaluation of specific urinary peptide levels under different disease conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The patients in different CKD groups differed from each other with the incidence of hypertension and diabetes, which is logical, since they are diseases that cause kidney dysfunction. Since diabetes results in significant metabolic alterations reflected in urine other than just presence of glucose and proteins alone 42,43 , we performed additional analyses to exclude the possibility that the classification of CKD is rather due to diabetes-related factors and confirmed that the results are not related with diabetes.…”
Section: Discussionmentioning
confidence: 80%